As associações empresariais e o processo constituinte de 1987- 88 - Troiano, Mariele (2012)
This research aims to understand how interests of the entrepreneurs class were represented in the constituent process of 1987-88, through the mapping of the actors involved, they parliamentary or not. As analytical approach, we start from the general idea that Federation of Industries of São Paulo State (FIESP) is an institutionalized organization and relevant activity in the Brazilian political and economic framework since its inception, including the constitutional process, the only federation, representing the entrepreneurs class was invited to a public hearing on the National Constituent Assembly. In analyzing the performance of entrepreneurs class in decision-making arena at the Constituent Assembly, noticed a proliferation of representative associations, which can be understood as a result of ineffective representation of FIESP. Through explanations of path dependency is possible to observe the maintenance of historical legacies of the organization, based on the corporatist system, as the main factor of its incapacity to represent. Based in the actions of the political actors that are involved, we can deduce that the entrepreneurs didn t have an effective representation at the constituent process. The actors actions could be comprehended as distinct products of the corporativist system that use to interfere in the way of the acting justified by the absence of a balance between the fundamental business characteristic of ANC and their methods. As methodology, was used minutes of the National Congress, literature review and press materials available at the Senate s site.